Attachment research and anti-racism: learning from Black and Brown scholars - Causadias, Jose M.; Morris, Kamryn S.; Carcamo, Rodrigo A.; Neville, Helen A.; Noblega, Magaly; Salinas-Quiroz, Fernando; Silva, Jaime R. (My University, 2022)
Preliminary evidence suggests that people and scholars of African and/or Latin American and Caribbean origin are often under-represented in mainstream attachment scholarship. In this commentary, we highlight the difficulty of conducting attachment theory research outside of the United States, particularly in Latin American countries. We reflect on the contributions by the authors of this special issue . We also identify (a) ways in which to center the experiences of Black and Brown people and scholars to push the field toward antiracism, and (b) the challenges of attachment theory and research in becoming anti-racist by considering the structural nature of racism.
Keywords: attachment; racism; anti-racism